Pandémie de Covid-19 et institutionnalisation de l'enseignement à distance dans les universités québécoises - Patrick Pelletier; Anne Mesny (Centre National d'Enseignement à Distance, 2021)
In this article, we question the impacts of the Covid-19 pandemic on the institutionalization of distance learning in Quebec universities. We compare the institutional logics supporting distance learning before the pandemic, with the arguments put forward since the beginning of the pandemic and the forced switch to distance learning in universities that used to rely primarily on face-to-face teaching. Our analysis is based, on one hand, on governmental and public/semi-public sector reports published before the pandemic and, on the other hand, on press articles published from March 2020 until June 2021. We suggest that a new institutional logic, based on the notions of flexibility, choice and hybridity, might be at stake regarding distance learning in traditional universities.